2013
DOI: 10.1292/jvms.12-0451
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping Assays for the Canine Degenerative Myelopathy-Associated c.118G>A (p.E40K) Mutation of the <i>SOD1</i> Gene Using Conventional and Real-Time PCR Methods: A High Prevalence in the Pembroke Welsh Corgi Breed in Japan

Abstract: ABSTRACT. Canine degenerative myelopathy is an adult-onset, progressive neurodegenerative disease that occurs in multiple dog breeds, particularly Pembroke Welsh Corgis. Recently, a degenerative myelopathy-associated mutation of the canine SOD1 gene was identified as c.118G>A (p.E40K). In the present study, genotyping assays using conventional and real-time PCR methods were developed, and a preliminary genotyping survey was performed on 122 randomly selected Pembroke Welsh Corgis without any degenerative myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…The SOD1:c.118G > A mutation, associated with CDM, was originally identified in a genome-wide association study and characterised by sequence-based typing [ 13 ]. Recent studies have used conventional and real-time PCR techniques to develop more rapid and cost-effective methods of genotyping dogs for this particular mutation [ 14 16 ]. The present study employed PCR followed by RFLP analysis, utilising the Eco571 enzyme, demonstrating that this technique allows rapid and simple genotyping dogs for the SOD1:c.118G > A mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The SOD1:c.118G > A mutation, associated with CDM, was originally identified in a genome-wide association study and characterised by sequence-based typing [ 13 ]. Recent studies have used conventional and real-time PCR techniques to develop more rapid and cost-effective methods of genotyping dogs for this particular mutation [ 14 16 ]. The present study employed PCR followed by RFLP analysis, utilising the Eco571 enzyme, demonstrating that this technique allows rapid and simple genotyping dogs for the SOD1:c.118G > A mutation.…”
Section: Discussionmentioning
confidence: 99%
“…All dogs with A/A or A/G genotypes were PWC, while the three other dogs carrying G/G were two Beagles and a Maltese. The genotypes of the dogs used in the present study were determined using a previously reported real-time PCR method (Chang et al, 2013). Formalin-fixed paraffin-embedded sections of the caudal thoracic spinal cord were prepared from each dog.…”
Section: Immunohistochemistry Of Spinal Cordsmentioning
confidence: 99%
“…In a recent study (Chang et al, 2013), genotyping assays using conventional and real-time PCR methods were developed, and a preliminary genotyping survey was performed on 122 randomly selected PWCs without any CDM-related clinical signs, to determine the current allele frequency in Japan. Both of the assays provided clear-cut genotyping.…”
Section: Genetic and Molecular Findingsmentioning
confidence: 99%